Photoinduced tensile deformation of azo polyimide ellipsoidal particles and preparation method thereof

The preparation of azo polyimide ellipsoid particles through solution self-assembly and phototension technology has solved the problem of the micromorphic polyimide in the prior art affecting the performance of lithium-ion batteries, and achieved better heat resistance and stability.

CN116041955BActive Publication Date: 2025-03-25CHONGQING UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211467798.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-03-25
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The micromorphology of existing polyimides affects powdering and agglomeration, and thus affects lithium ion diffusion, lithium ion charge transfer, and battery cycle temperature.

Method used

Azo polyimide microspheres were prepared by solution self-assembly method, and phototension deformation of the microspheres was induced by linear polarization laser irradiation to prepare azo polyimide ellipsoid particles with controllable size and morphology.

Benefits of technology

The size and morphology of azo polyimide ellipsoid particles are controlled, and as the negative electrode material of lithium-ion batteries, it has better heat resistance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116041955B_ABST
    Figure CN116041955B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation and processing of nanoparticles of high-performance and functional responsive polymers, and discloses a photo-induced tensile deformed azo polyimide ellipsoidal particle and a preparation method thereof. The average minor axis size of the photo-induced tensile deformed azo polyimide ellipsoidal particle is 394-546 nm; the average molecular weight of azo polyimide is 7000-250000; the aspect ratio of the photo-induced tensile deformed azo polyimide ellipsoidal particle is 1.0-3.0. The preparation method of the photo-induced tensile deformed azo polyimide ellipsoidal particle comprises: irradiating azo polyimide microspheres with linear polarized laser to induce the azo polyimide microspheres to stretch and deform along the polarization direction of light, thereby preparing azo polyimide ellipsoidal particles in a controlled manner. The azo polyimide ellipsoidal particle of the present invention has better heat resistance and stability when used as a negative electrode material of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and processing of nanoparticles of high-performance and functionally responsive polymers, and in particular relates to a photoinduced tensile deformed azo polyimide ellipsoidal particle and a preparation method thereof. Background Art

[0002] At present, organic carbonyl compounds are typical compounds with redox activity. The main chain structure of polyimide contains a large number of carbonyl active groups, which can receive and release lithium ions during the charge and discharge process of lithium batteries, showing electrochemical activity. At the same time, polyimide has the characteristics of structural stability, chemical stability and high temperature resistance, which is very suitable as a negative electrode material for lithium-ion batteries. Electrochimica Acta, 2017, 229: 387-395 reported that the theoretical capacity of lithium batteries with polyimide as electrode materials reached 400mAh / g, exceeding the 372mAh / g of graphite. However, the microscopic morphology of polyimide not only affects its pulverization and agglomeration, but also affects lithium ion diffusion, lithium ion charge transfer, battery cycle temperature, etc. Applied Surface Science, 2017, 425: 1082-1088 reported a polyimide material with flower-like nanoparticles, which performed well in terms of battery capacity, rate and cycle stability, and can improve lithium storage performance. Journal of Materials Chemistry, 2010: 20: 5405-5410. The nanosheet arrays with micro / nano structures prepared by polyimide exhibit excellent electrochemical performance in lithium storage and water electrolysis. Therefore, the design and controllable processing of the microstructure of polyimide has an important impact on its application as anode material in lithium batteries.

[0003] Journal of the American Chemical Society, 2005, 127: 2402-2403; Polymer, 2015, 60: 292-301 reported two azo polymers synthesized based on epoxy groups. Azo polymer microspheres were prepared by dropwise addition of a poor solvent. Under 488nm linear interference polarized laser and 488nm linear polarized laser vertical irradiation, the azo polymer microspheres were photoinduced to stretch and deform into ellipsoidal particles. By adjusting the size of the azo polymer microspheres, as well as the laser power and laser irradiation time, the size, aspect ratio, etc. of the azo polymer ellipsoidal particles can be adjusted.

[0004] Obviously, the solution self-assembled microspheres based on epoxy-synthesized azo polymers and their photoinduced tensile deformation can controllably prepare ellipsoidal particles, which can realize technological innovation and breakthroughs for the controllable preparation of azo polyimide with ellipsoidal particle micromorphology and its application in lithium-ion batteries.

[0005] Through the above analysis, the problems and defects of the existing technology are as follows: the microscopic morphology of the existing polyimide affects powdering and agglomeration, and also affects lithium ion diffusion, lithium ion charge transfer and battery cycle temperature. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a kind of azo polyimide ellipsoidal particles with photoinduced tensile deformation and a preparation method thereof, and in particular relates to a method for preparing azo polyimide ellipsoidal particles with high photoresponsiveness and heat resistance and an application thereof as an organic negative electrode material in lithium ion batteries.

[0007] The present invention is achieved by providing a photoinduced tensile deformed azo polyimide ellipsoidal particle, wherein the average minor axis size of the photoinduced tensile deformed azo polyimide ellipsoidal particle is 394-546 nm; the average molecular weight of the azo polyimide is 7000-250000; and the aspect ratio of the photoinduced tensile deformed azo polyimide ellipsoidal particle is 1.0-3.0.

[0008] Furthermore, the average molecular weight of the azo polyimide is 14,000 to 100,000.

[0009] Another object of the present invention is to provide a method for preparing photoinduced tensile deformed azo polyimide ellipsoidal particles, which comprises: irradiating azo polyimide microspheres with linearly polarized laser to induce tensile deformation of the azo polyimide microspheres along the polarization direction of light, thereby preparing azo polyimide ellipsoidal particles in a controlled manner.

[0010] Furthermore, the wavelength of the linearly polarized laser is 488 nm, and the irradiation power is 10 to 200 mW / cm 2 , irradiation time is 0 to 60 minutes.

[0011] Furthermore, the preparation method of azo polyimide microspheres includes: adding an appropriate amount of deionized water dropwise to the azo polyimide solution; after adding the deionized water dropwise, immediately adding 20 mL of deionized water to the azo polyimide microsphere dispersion at one time to prepare the azo polyimide microspheres.

[0012] Further, the concentration of the azo polyimide solution is 0.1 to 10 mg / mL;

[0013] The solvent for dissolving the azo polyimide is any one or more of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.

[0014] Furthermore, the amount of deionized water added is 1.0 to 3.0 mL; and the speed of adding deionized water is 1.8 to 20 mL / h.

[0015] Further, the structural formula of azo polyimide is shown below:

[0016]

[0017] Further, the preparation method of azo polyimide comprises the following steps:

[0018] (1) using p-nitroaniline to prepare a diazonium salt, adding it dropwise to a 95% molar ratio N,N-dihydroxyethylaniline solution in N,N-dimethylformamide under ice bath conditions to react for 12 hours, and preparing an intermediate product 1 by precipitation, filtration, purification and drying;

[0019] (2) using pyridine as a catalyst, reacting equimolar amounts of the intermediate product 1 and 1,2,4-trimellitic anhydride chloride in a tetrahydrofuran solution at room temperature for 24 h, and purifying by recrystallization to prepare the intermediate product 2;

[0020] (3) using potassium carbonate as a catalyst, an equimolar amount of p-nitrophenol and 1,6-dibromohexane in an N,N-dimethylformamide solution were reacted at 110° C. for 24 h, and an intermediate product 3 was prepared by precipitation, filtration, purification and drying;

[0021] (4) using stannous chloride as a reducing agent, reacting the intermediate product 3 in a hydrochloric acid solution at 50° C. for 24 h, and preparing the intermediate product 4 by precipitation, filtration, purification and drying;

[0022] (5) An azo polyamic acid solution of intermediate product 5 was prepared by reacting equimolar amounts of intermediate product 2 and intermediate product 4 in an N,N-dimethylformamide solution in an ice bath for 48 h;

[0023] (6) adding anhydrous glacial acetic acid and pyridine to the intermediate product solution, reacting at room temperature for 48 hours under nitrogen atmosphere protection; preparing an azo polyimide solution by chemical ring closure imidization of azo polyamic acid, and preparing an azo polyimide material by precipitation, filtration, purification and drying.

[0024] Another object of the present invention is to provide an application of the azo polyimide and azo polyimide microspheres in preparing organic negative electrode materials for lithium ion batteries.

[0025] Another object of the present invention is to provide a use of the photoinduced tensile deformed azo polyimide ellipsoidal particles as an organic negative electrode material in the preparation of lithium ion batteries.

[0026] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0027] The present invention belongs to the technical field of preparation and processing of nanoparticles of high-performance and functional responsive polymers, and relates to a preparation method and application of azo polyimide ellipsoidal particles with high photoresponsiveness and heat resistance. The carbonyl active groups, benzene rings, aromatic heterocycles and other structures on the polyimide main chain can be used as active sites for redox reactions, can accept lithium ions during the charging process, and exhibit electrochemical activity; at the same time, its structural stability, chemical stability and high temperature resistance have great potential as the negative electrode material of lithium-ion batteries. However, the microscopic morphology of polyimide has a great influence on the performance of its lithium-ion battery, such as cycle stability, lithium ion diffusion path and lithium ion charge transfer. The present invention is based on a method for self-assembly of colloidal spheres in a solution and a processing and preparation technology for photoinduced stretching deformation of azo colloidal spheres into ellipsoidal particles, to achieve azo polyimide ellipsoidal particles and their preparation method, which can be applied in the negative electrode material of lithium-ion batteries.

[0028] In order to obtain better lithium-ion battery performance by regulating the microstructure of polyimide used as a negative electrode material, the present invention provides an azo polyimide ellipsoidal particle and a preparation method thereof.

[0029] The azo polyimide ellipsoidal particles provided by the present invention have controllable size and morphology and have better heat resistance and stability when used as negative electrode materials of lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 It is a schematic diagram of the morphology structure of azo polyimide ellipsoidal particles subjected to photoinduced tensile deformation provided by an embodiment of the present invention;

[0032] Figure 2 The invention provides a reaction product of a diazonium salt prepared by using p-nitroaniline and N,N-dihydroxyethylaniline. 1 H-NMR spectrum;

[0033] Figure 3 The embodiment of the present invention provides Figure 2 The dianhydride monomer synthesized by reacting the compound in the formula (C) with 1,2,4-trimellitic anhydride chloride 1 H-NMR spectrum;

[0034] Figure 4 The diamine monomer product provided by the embodiment of the present invention is 1 H-NMR spectrum;

[0035] Figure 5 The azo polyamic acid polymer provided by the embodiment of the present invention is 1 H-NMR spectrum;

[0036] Figure 6 The azo polyimide polymer provided by the embodiment of the present invention is 1 H-NMR spectrum;

[0037] Figure 7 It is a transmission electron microscope picture of the solution self-assembled azo polyimide microspheres provided in the embodiment of the present invention. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] In view of the problems existing in the prior art, the present invention provides a photoinduced tensile deformed azo polyimide ellipsoidal particle and a preparation method thereof. The present invention is described in detail below in conjunction with the accompanying drawings.

[0040] In order to enable those skilled in the art to fully understand how to implement the present invention in detail, this section is an explanatory embodiment that expands and describes the technical solution of the claims.

[0041] like Figure 1 As shown, in the azo polyimide ellipsoidal particles provided by the embodiment of the present invention, the average molecular weight of the azo polyimide is 7000-250000, preferably 14000-100000; the average minor axis (D) size of the azo polyimide ellipsoidal particles is 394-546 nm, and the aspect ratio of the ellipsoidal particles is 1.0-3.0.

[0042] The azo polyimide ellipsoidal particles provided in the embodiment of the present invention are realized by vertically irradiating the azo polyimide microspheres with a 488nm linear polarized laser. The azo polyimide colloidal sphere dispersion is dripped onto the surface of a copper mesh or a silicon wafer, and the laser irradiation power (10-150mW / cm 2 ) and irradiation time (0-60min) were used to regulate the aspect ratio and morphology of the azopolyimide ellipsoidal particles.

[0043] The azopolyimide microspheres provided in an embodiment of the present invention are prepared by a self-assembly method of dropwise adding a poor solvent to a good azopolyimide solution. By optimizing the self-assembly conditions, azopolyimide microspheres of uniform size can be obtained. The specific operation steps are as follows: First, under uniform stirring conditions, add an appropriate amount of deionized water to 1mL of azopolyimide N,N-dimethylformamide solution at an appropriate drop rate. After the addition of deionized water is completed, 20mL of deionized water is quickly added at one time to freeze the azopolyimide aggregate structure; secondly, after the self-assembly is completed, the azopolyimide colloidal sphere dispersion is allowed to stand for 3 days, and the N,N-dimethylformamide solvent molecules are replaced by dialysis.

[0044] The solvent of the azo polyimide solution provided in the embodiment of the present invention is any one or more of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.

[0045] The concentration of the azo polyimide solution provided in the embodiment of the present invention is 0.1 to 10 mg / mL, preferably 0.2 to 5 mg / mL.

[0046] The drop amount of the deionized water provided in the embodiment of the present invention is 1.0 to 3.0 mL, preferably 1.5 to 2.5 mL; the drop speed of the deionized water is 1.8 to 20 mg / mL.

[0047] The azo polyimide polymer provided in the embodiment of the present invention is a polyimide polymer containing azobenzene functional groups in the side chain, and its typical structural formula is:

[0048]

[0049] The method for preparing an azo polyimide polymer provided in an embodiment of the present invention comprises synthesizing a dianhydride compound containing an azobenzene functional group, synthesizing a diamine compound, synthesizing a polyamic acid polymer having an azobenzene functional group as a side chain, and synthesizing a polyimide polymer having an azobenzene functional group as a side chain.

[0050] The synthesis and preparation of the dianhydride compound containing azobenzene functional group provided in the embodiment of the present invention, the synthesis reaction flow is as follows:

[0051]

[0052] Among them, R1 is any one of nitro, carboxyl, cyano, trifluoromethyl or methoxy functional groups, preferably a nitro functional group.

[0053] Taking p-nitroaniline as an example, a mixed solution of p-nitroaniline (2.07 g, 0.015 mol) in acetic acid (5 mL) and propionic acid (5 mL) was prepared, and concentrated sulfuric acid (2 mL) and sodium nitrite (1.38 g, 0.02 mol) aqueous solution (6 mL) were added dropwise in an ice bath condition to prepare a nitro-containing diazonium salt solution; secondly, N,N-dihydroxyethylaniline (2.55 g, 0.014 mol) was dissolved in N,N-dimethylformamide (100 mL), and the diazonium salt solution was added dropwise into the N,N-dihydroxyethylaniline solution under ice bath stirring condition, and after the addition was completed, the mixture was reacted for 12 hours under ice bath condition of 0°C; finally, after the reaction was completed, the reactant solution was added dropwise into 300 mL of uniformly stirred water, and after standing, it was filtered by suction, and washed with deionized water repeatedly for 2 to 3 times, and purified and dried to obtain an intermediate product.

[0054] A tetrahydrofuran solution of the intermediate product and 1,2,4-trimellitic anhydride chloride in an equal molar ratio is prepared, pyridine (200% mol) is added to the tetrahydrofuran solution of the intermediate product, and 1,2,4-trimellitic anhydride chloride is added dropwise to the solution of the intermediate product 1; after the addition is completed, the reaction is continued at room temperature for 24 hours; after the reaction is completed, acetic anhydride is used for recrystallization and purification to prepare a dianhydride compound containing an azobenzene functional group.

[0055] The synthesis reaction process of the diamine compound provided in the embodiment of the present invention is as follows:

[0056]

[0057] Wherein, m is a dibromo-substituted alkyl group with carbon number of 2, 3, 4, 5, 6, 7, 8, 9, 10; more preferably 4 and 6.

[0058] Taking 1,6-dibromohexane as an example, potassium carbonate catalyst was added to a mixture of p-nitrophenol and 1,6-dibromohexane in N,N-dimethylformamide in an equimolar ratio, and the mixture was reacted at 110°C for 24 hours. An intermediate product was prepared by precipitation, filtration, washing, purification and drying. Secondly, the intermediate product was reacted in a hydrochloric acid solution for 24 hours (50°C) using a stannous chloride reducing agent, and a diamine compound was synthesized by precipitation, filtration, purification and drying.

[0059] The synthesis and preparation of the polyamic acid polymer having azobenzene functional groups as the side chains provided in the embodiment of the present invention is as follows:

[0060]

[0061] Taking p-nitroaniline and 1,6-dibromohexane as examples, the diacid anhydride monomer and diamine monomer containing azobenzene functional groups synthesized above were reacted in an N,N-dimethylformamide solution in an equal molar ratio under ice bath conditions for 48 hours to prepare a polyamic acid polymer solution with azobenzene functional groups in the side chains.

[0062] In addition to the synthetic diamine monomer, the diamine monomer for synthesizing polyamic acid provided in the embodiment of the present invention can also be one or more of ethylenediamine, propylenediamine, butylenediamine, pentanediamine or hexamethylenediamine.

[0063] The solvent in the reaction provided in the embodiment of the present invention may be any one or more of N,N-dimethylacetamide, N-methylpyrrolidone or dimethyl sulfoxide, in addition to N,N-dimethylformamide.

[0064] The synthesis preparation of the polyimide with azobenzene functional group as the side chain provided by the embodiment of the present invention is as follows: first, anhydrous glacial acetic acid and pyridine are added to a polyamic acid polymer solution with azobenzene functional group as the side chain, and the mixture is reacted at room temperature for 48 hours; secondly, after the reaction is completed, a large amount of methanol is added to precipitate the polymer, and the target product is obtained by filtering and drying: a polyimide with azobenzene functional group as the side chain.

[0065] Example 1

[0066] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0067] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0068] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0069] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0070] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 20min.

[0071] Example 2

[0072] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0073] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0074] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0075] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0076] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 10min.

[0077] Example 3

[0078] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0079] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0080] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0081] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0082] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 40min.

[0083] Example 4

[0084] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0085] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0086] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0087] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0088] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 50mW / cm 2 , the irradiation time is 20min.

[0089] Example 5

[0090] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0091] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0092] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0093] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0094] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 150mW / cm 2 , the irradiation time is 20min.

[0095] Example 6

[0096] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0097] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0098] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0099] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 3.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0100] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 20min.

[0101] Example 7

[0102] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0103] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0104] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0105] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 0.3 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 7.2 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0106] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 20min.

[0107] Example 8

[0108] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0109] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0110] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0111] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 3.6 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0112] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 20min.

[0113] Example 9

[0114] The embodiment of the present invention utilizes a post-diazo coupling method to prepare a diazonium salt from p-nitroaniline, and reacts the diazonium salt with N,N-dihydroxyethylaniline to obtain an intermediate product; the intermediate product is further reacted with 1,2,4-trimellitic anhydride chloride to obtain a dianhydride monomer containing an azobenzene functional group.

[0115] The monomer of the diamine is prepared by using the substitution reaction of p-nitrophenol and 1,6-dibromohexane to produce an intermediate product containing two nitrobenzene functional groups. Under the action of a stannous chloride reducing agent, the intermediate product containing nitrobenzene is reduced to obtain a monomer of the diamine.

[0116] The synthesized azobenzene functional group dianhydride monomer and diamine are reacted in an equimolar ratio under ice bath conditions for 48 hours to prepare a polyamic acid solution containing azobenzene functional groups on the side chain; the azo polyamic acid solution is subjected to chemical ring closure amidation using anhydrous glacial acetic acid and pyridine to prepare a polyimide containing azobenzene functional groups on the side chain; and an azo polyimide material is prepared by precipitation, filtration, purification and drying.

[0117] Using N,N-dimethylformamide solvent, prepare azo polyimide solution with a concentration of 1.0 mg / mL. Take 1 mL of azo polyimide solution, and add 2 mL of deionized water dropwise at a rate of 14.4 mL / h using a microinjection pump under stable stirring conditions. Then add 20 mL of deionized water at one time, and finally use a dialysis bag to dialyze the N,N-dimethylformamide solvent to prepare a dispersion of azo polyamide imide microspheres.

[0118] Use a pipette to drop the dispersed azo polyimide microspheres onto a copper mesh or silicon wafer. Leave it at room temperature for 3 days until the solvent evaporates completely. Then use a solid-state laser to emit a linearly polarized 488nm laser to irradiate the surface of the azo polyimide microspheres vertically. The laser irradiation power is 100mW / cm 2 , the irradiation time is 20min.

[0119] The size parameters of the azo polyimide ellipsoidal particles prepared in the above-mentioned Examples 1 to 9 are shown in Table 1. As can be seen from Table 1, by self-assembling azo polyimide microspheres from a solution and utilizing their photoinduced tensile deformation function under laser irradiation, ellipsoidal polyimide particles can be successfully prepared. Compared with Example 1, Examples 2 and 3 can control the deformation degree of the azo polyimide ellipsoidal particles by adjusting the laser irradiation time. The longer the laser irradiation time, the greater the average aspect ratio. Compared with Example 1, Examples 4 and 5 can also control the degree of formation of the azo polyimide ellipsoidal particles by adjusting the laser irradiation power. The greater the laser irradiation power, the greater the average aspect ratio. Compared with Example 1, Examples 6 and 7 can control the minor axis size of the azo polyimide ellipsoidal particles by adjusting the solution concentration of the azo polyimide polymer during the solution self-assembly process. As the concentration of the polymer solution increases, the average minor axis size increases. Compared with Example 1, Examples 8 and 9 can adjust the minor axis size of the polyimide ellipsoidal particles by adjusting the water droplet addition rate during the solution self-assembly process. The faster the water droplet addition rate, the larger the average minor axis size.

[0120] Table 1 Experimental scheme of Examples 1 to 9 and size parameters of azo polyimide ellipsoidal particles

[0121]

[0122] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A photoinduced tensile deformation of azo polyimide ellipsoidal particles, characterized in that: The average minor axis size of the photoinduced tensile deformed azo polyimide ellipsoidal particles is 394-546 nm; the average molecular weight of the azo polyimide is 7000-250000; the aspect ratio of the photoinduced tensile deformed azo polyimide ellipsoidal particles is 1.0-3.0, and the aspect ratio is not 1; The structural formula of azo polyimide is shown below:

2. The photoinduced tensile deformed azo polyimide ellipsoidal particles according to claim 1, characterized in that: The average molecular weight of azo polyimide is 14,000 to 100,000.

3. A method for preparing photoinduced tensile deformable azo polyimide ellipsoidal particles according to any one of claims 1 to 2, characterized in that: The method for preparing photoinduced tensile deformation azo polyimide ellipsoidal particles comprises: using linear polarized laser to irradiate azo polyimide microspheres, inducing the azo polyimide microspheres to stretch and deform along the polarization direction of light, thereby controllably preparing azo polyimide ellipsoidal particles.

4. The method for preparing photoinduced tensile deformation azo polyimide ellipsoidal particles according to claim 3, characterized in that: The wavelength of the linearly polarized laser is 488nm, and the irradiation power is 10-200mW / cm 2 , the irradiation time is 0 to 60 minutes, and the irradiation time is not 0.

5. The method for preparing photoinduced tensile deformation azo polyimide ellipsoidal particles according to claim 3, characterized in that: The preparation method of azo polyimide microspheres comprises: adding an appropriate amount of deionized water drop by drop into a solution of azo polyimide; after adding the deionized water drop by drop, immediately adding 20 mL of deionized water into the azo polyimide microsphere dispersion at one time to prepare azo polyimide microspheres; The concentration of azo polyimide solution is 0.1 to 10 mg / mL; The solvent for dissolving azo polyimide is any one or more of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; The amount of deionized water added is 1.0 to 3.0 mL; the speed of deionized water added is 1.8 to 20 mL / h.

6. The method for preparing photoinduced tensile deformation azo polyimide ellipsoidal particles according to claim 5, characterized in that: The amount of deionized water added is 1.5 to 2.5 mL; the concentration of the azo polyimide solution is 0.2 to 5 mg / mL.

7. The method for preparing photoinduced tensile deformation azo polyimide ellipsoidal particles according to claim 4, characterized in that: The preparation method of azo polyimide comprises the following steps: (1) using p-nitroaniline to prepare a diazonium salt, adding it dropwise to a 95% molar ratio N,N-dihydroxyethylaniline solution in N,N-dimethylformamide under ice bath conditions to react for 12 hours, and preparing an intermediate product 1 by precipitation, filtration, purification and drying; (2) using pyridine as a catalyst, an intermediate product 2 was prepared by reacting equimolar amounts of the intermediate product 1 and 1,2,4-trimellitic anhydride chloride in a tetrahydrofuran solution at room temperature for 24 h, and then purified by recrystallization; (3) Using potassium carbonate as a catalyst, equimolar amounts of p-nitrophenol and 1,6-dibromohexane in N,N-dimethylformamide solution were reacted at 110° C. for 24 h, and intermediate product 3 was prepared by precipitation, filtration, purification and drying; (4) using stannous chloride as a reducing agent, reacting the intermediate product 3 in a hydrochloric acid solution at 50° C. for 24 h, and preparing the intermediate product 4 by precipitation, filtration, purification and drying; (5) An azo polyamic acid solution of intermediate product 5 was prepared by reacting equimolar amounts of intermediate product 2 and intermediate product 4 in an N,N-dimethylformamide solution in an ice bath for 48 h; (6) Anhydrous glacial acetic acid and pyridine were added to the solution of the intermediate product 5, and the mixture was reacted at room temperature for 48 hours under a nitrogen atmosphere; an azo polyimide solution was prepared by chemical ring-closing imidization of azo polyamic acid, and an azo polyimide material was prepared by precipitation, filtration, purification and drying.

8. Use of the photoinduced tensile deformed azo polyimide ellipsoidal particles as claimed in claim 1 as an organic negative electrode material in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Preparation and application of photoresponsive polymer-covalent organic framework blended membrane

    CN113856493A

  • Phthalocyanine photosensitive materials for electrophotography and processes for making the same

    US5087540A